PEMANFAATAN SUMBER DAYA TEKNOLOGI DALAM PEMBELAJARAN INDAHNYA MEMBANGUN MAHLIGAI RUMAH TANGGA - Azkia, Nabilla; Dwika, Mariza Lia; S., Elly Syafitry; Yuli, Yuli; Nuzli, Muhammad; Maspan, Maspan (Sosio Akademika, 2025)
Technology is an important tool used by most people today because technology has covered all aspects of life, including education. This study aimed to determine whether the technological resources in household management learning at MAN 1 Merangin have been met or not. The study was conducted using qualitative research methods, using observation, interview, and documentation data collection methods. And the results of the study found that in household management learning at MAN 1 Merangin, technological resources were not utilized, especially in carrying out practices such as those carried out in household management learning such as Applications such as "Love Nudge" to improve couple communication and "Cozi" for managing household tasks can help in living a family life; and such as Social Media: Following pages and groups on social media that focus on family and marriage topics can provide insight and support from the wider community, as well as other learning technology resources.